Does low latency trading improve market efficiency? A discussion - Erhard, Ryan; Sloan, Richard G. (Journal of Accounting and Economics, 2020)
Chordia and Miao (2020) provide evidence that low-latency trading (LLT) improves the long-term informational efficiency of stock prices. This discussion raises two primary concerns with their analysis. First, the mechanism through which LLT enhances long-term efficiency is unclear. Second, CM's measure of LLT trading activity is correlated with non-LLT trading activity, which may in turn cause the documented improvements in efficiency. We close by proposing an alternative explanation—changes in market microstructure have had a bifurcated impact on liquidity, enhancing efficiency for large and liquid stocks, but not for small and illiquid stocks.